The political consequences of gradual engineering in Popper's thought - Afsharzadeh Hassan; Sohrabzadeh Abbas; Golshani Alireza (Kom: Časopis za Religijske Nauke)
This article seeks to examine the political consequences of the gradual engineering of Popper's thought. Popper's solution is realistic and intends to reduce problems by giving some power to the state in facing social disasters. Ultimately, Popper's strategy of achieving the goals of the welfare state is the so-called gradual social engineering, a method of searching for and combating the greatest and most profound societal pitfalls. Given this, the main question addressed in this paper is what the political consequence of the gradual engineering in Popper's thought is. In response, this hypothesis has been suggested that the political system based on liberal democracy is the political consequence of the gradual engineering of Popper's thought. In Popper's liberal-democratic political system, which is the end result of gradual engineering, the government has a duty to reduce human suffering and achieve prosperity. In Popper's social engineering, first, an ideal goal is set for the future and then it is tried to move towards that goal. In his view, when gradual engineering is properly implemented by the government, true liberal democracy can be achieved and human suffering can be reduced.